2007
DOI: 10.3892/ijmm.19.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuropeptides B and W on the rat pituitary-adrenocortical axis: In vivo and in vitro studies

Abstract: Abstract. Neuropeptides (NP) B and W are hypothalamic peptides involved in the regulation of feeding and neuroendocrine axes. Evidence has been provided that NPB and NPW act on both the central and the peripheral branches of the rat hypothalamic-pituitary-adrenocortical axis, and we carried out in vivo and in vitro studies to gain insight into this topic. Reverse transcription-polymerase chain reaction showed the expression of NPB, NPW and their receptors in both adrenal cortex (zonae glomerulosa and fascicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…NPB and NPW were shown to pharmacologically stimulate adrenal glucocorticoid secretion by an ACTH-independent mechanism. It was also reported that NPW stimulates in vitro aldosterone secretion by enhancing the release of medullary catecholamines, which activate beta-adrenoceptors located on zona glomerulosa cells (Hochol et al, 2007). …”
Section: Biological Activities Of Npb and Npwmentioning
confidence: 99%
See 1 more Smart Citation
“…NPB and NPW were shown to pharmacologically stimulate adrenal glucocorticoid secretion by an ACTH-independent mechanism. It was also reported that NPW stimulates in vitro aldosterone secretion by enhancing the release of medullary catecholamines, which activate beta-adrenoceptors located on zona glomerulosa cells (Hochol et al, 2007). …”
Section: Biological Activities Of Npb and Npwmentioning
confidence: 99%
“…Expression of Npb , Npw , and Npbwr1 mRNA in both the adrenal cortex and adrenal medulla has been reported (Andreis et al, 2005; Mazzocchi et al, 2005; Hochol et al, 2007). NPB and NPW were shown to pharmacologically stimulate adrenal glucocorticoid secretion by an ACTH-independent mechanism.…”
Section: Biological Activities Of Npb and Npwmentioning
confidence: 99%
“…It should also be noted that galanin is involved in the central control of feeding (2,3), and that other peptides playing a similar role (e.g. neuropeptide-Y, neuropeptide-W, leptin, orexins and cholecystokinins) are able to control glucocorticoid secretion acting on both the central and the peripheral branch of the hypothalamic-pituitary-adrenal axis (34)(35)(36)(37)(38). In addition, the possible adrenocortical secretagogue action of another preprogalanin-derived peptide, the galanin-like peptide (GALP), should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Methods applied were described earlier (21,(37)(38)(39)(40)(41). Applied primers for studies of NPB, NPW, NPBWR1 and similar to NPBWR2 gene expression (Table I) were purchased from the Laboratory of DNA Sequencing and Oligonucleotide Synthesis, Institute of Biochemistry and Biophysics, Polish Academy of Sciences, Warsaw.…”
Section: Methodsmentioning
confidence: 99%